Religion and Culture Education: Understanding the Interplay and Significance - Rajiman Andrianus Sirait; Olis Olis (Anugerah : Jurnal Pendidikan Kristiani dan Kateketik Katolik, 2024)
Religion and culture are closely interconnected facets of human society that exert a profound influence on individuals' belief systems, moral principles, and actions. The discipline of religious and cultural education plays a pivotal role in advancing intercultural comprehension, cultivating societal unity, and creating a sense of global citizenship. This academic paper examines the dynamic relationship between religion and culture within educational environments, underscoring the significance of integrating religious and cultural literacy within formal educational institutions. This research is to present a comprehensive analysis of the contemporary status of education in religion and culture. To achieve this objective, a wide range of scholarly sources, including as academic journals, books, and educational reports, have been consulted. The primary focus of this study is to identify the existing obstacles in religion and culture education and propose recommendations for its successful implementation.